Sand and The City: The historical geography of sand mining in Jeneberang River and its relation to urban development in South Sulawesi - Kusumaningrum, Dwiyanti; Hafsari, Tria Anggita; Syam, Lukman (ETNOSIA : Jurnal Etnografi Indonesia, 2021)
This exploratory research aims to elaborate the historical geography of sand mining in Jeneberang River and analyze its relation to urban development in South Sulawesi. This paper attempts to comprehensively explain and enrich the literature on Jeneberang start from physical setting of Jeneberang River to the history of Makassar and transformation of traditional houses to explain how sand perceived as a commodity and how sand mining has developed. We use a qualitative approach that emphasizes the interpretation of spatiotemporal morphology of sandbanks in Jeneberang River and investigate sand mining activities from time to time. The method consists of a study of Jeneberang historical literature, spatiotemporal analysis, in-depth interviews, and field observations. We find that sands have started to become a commodity since urban development began in South Sulawesi. With volcanic and marine sedimentary rocks dominate the region and the braided river morphology, Jeneberang River is rich of sand and gravel materials. The ‘modern’ architecture brought by the Dutch and South Sulawesi rebellion in 1950 has affected major transformation from wooden traditional houses to concrete-building houses, which indirectly affect the sand mining activities in Jeneberang. No more wooden and bamboo or palm leaves, but sand and gravel for concrete materials. In the current context, Makassar’s rapid urbanization and economic growth in have increased the demand of building materials from Jeneberang River. In addition, rapid urbanization has also been changed the livelihoods of local communities, especially in the suburb to cope with the urban development. Many people who previously work as farmers are now becoming sand miners because they perceive that sand mining is more profitable than agriculture.